FEEDBACK ANALYSIS OF PATIENTS IN A TERTIARY CARE HOSPITAL - Ali, Muhammad; Attiq, Saima; ., Shabana; Shah, Mahin; Nawaz, Naima (Pakistan Armed Forces Medical Journal, 2017)
Objective: To analyze feedback and pattern of response by patients over a period of two years in a tertiary care hospital.Study Design: Descriptive study.Place and Duration of Study: Quality Assurance Department of Combined Military Hospital Malir, from Jan 2014 till Dec 2015.Material and Methods: Combined Military Hospital Malir is a quality management System/International organization of standardization 9001-2008 certified since 2013 and has a well-established quality assurance department. Before conducting this study it was ensured that every department of the hospital has a prominently placed complaint/suggestion register along with the pre-designed feedback proformas. Patients feedbacks submitted spontaneously were collected from all 40 departments of the hospital on regular basis. All the data collected were then analyzed at the quality assurance department. Patients’ responses were broadly grouped into three major categories which were: Complaints, Suggestions and Compliments. These three major categories of feedbacks were analyzed in terms of frequency and percentages which were further analyzed against six parameters depending upon their relation. These parameters were hospital staff, hospital environment, medicine & treatment, infrastructure, hospital comforts and basic amenities. All the data were analyzed on SPSS 20.Results: In the year 2014, Combined Military Hospital received 1528 patients’ feedback from all the departments. A total of 1071 (70%) out of these were complaints, 153 (10%) were compliments and 304 (20%) were suggestions. In the year 2015, we received 593 patients’ feedback constituting 187 (32%) complaints, 258 (43%) compliments and 148 (25%) suggestions. Out of 1071 complaints majority 244 (23%) were related to basic amenities followed by 213 (20%) related to hospital environment. Complaints pertaining to staff behavior were 195 (18%) while 178 (17%) were directed towards medicines and treatment. About 170 (16%) people were not satisfied with the infrastructure of the hospital while only 71 (7%) people showed dissatisfaction towards hospital comforts. On comparing the results of year 2014 to 2015, we found that there was a reduction of 62% in total number of feedbacks (1528 to 593). Complaints declined by 82% (1071 to 187) while compliments increased from 10% to 43%. Most of the complaints were regarding basic amenities 41% (76) followed by 19% (35), 17% (31) and 16% (29) related to hospital comforts, medicines/treatment and staff respectively.Conclusion: In a public hospital set up most of the complaints are generated towards basic amenities like provision of quality food, clean drinking water and hygienic washrooms followed by hospital general environment and staff behavior. Simultaneously it is also found that timely action taken by board of doctors and administration on patients feedback and complaints minimize chances of their recurrence and increase the confidence of the patients towards an organisation in the form of compliments.